2020
DOI: 10.1111/clr.13577
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory performance and oral health‐related quality of life in edentulous maxillectomy patients: A cross‐sectional study to compare implant‐supported obturators and conventional obturators

Abstract: Objective:The aim of this cross-sectional study was to compare the masticatory performance and oral health-related quality of life (OHRQoL) of edentulous maxillectomy patients with and without implant-supported obturator prostheses. Material and methods:Nineteen edentulous maxillectomy patients with completed prosthetic obturator treatment in the upper jaw participated in this study. In nine patients, the obturator prosthesis was supported by implants in the remaining bone of the midface and/or skull base to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 50 publications
0
30
0
2
Order By: Relevance
“…Placing endosseous implants in the native bone of the maxilla will allow to improve retention of the obturator prosthesis and thereby increase the success of prosthetic rehabilitation. Patients with implant‐supported obturator prostheses have significantly better masticatory and oral function, and less discomfort during food intake than patients with a conventional obturator (Buurman, Speksnijder, Engelen, & Kessler, 2020). Studies which compared prosthetic obturation with reconstruction of a palatomaxillary defect demonstrated that there are some advantages to reconstruct the defects above obturation of these defects, in particular with regard to quality‐of‐life issues such as comfort, convenience and feelings of self‐consciousness (Rogers, Lowe, McNally, Brown, & Vaughan, 2003).…”
Section: Rehabilitation Of Maxillary Defectsmentioning
confidence: 99%
“…Placing endosseous implants in the native bone of the maxilla will allow to improve retention of the obturator prosthesis and thereby increase the success of prosthetic rehabilitation. Patients with implant‐supported obturator prostheses have significantly better masticatory and oral function, and less discomfort during food intake than patients with a conventional obturator (Buurman, Speksnijder, Engelen, & Kessler, 2020). Studies which compared prosthetic obturation with reconstruction of a palatomaxillary defect demonstrated that there are some advantages to reconstruct the defects above obturation of these defects, in particular with regard to quality‐of‐life issues such as comfort, convenience and feelings of self‐consciousness (Rogers, Lowe, McNally, Brown, & Vaughan, 2003).…”
Section: Rehabilitation Of Maxillary Defectsmentioning
confidence: 99%
“…A recently published systematic review describes a risk of selection bias and heterogeneous measurements for studies comparing masticatory efficiency 7 . Additionally, the different methods of measuring masticatory performance: mixing ability test, colour changing chewing gum, and sieving method used in maxillectomy patients 11‐13,21,25,29,33‐36 complicate the comparison of the study results.…”
Section: Discussionmentioning
confidence: 99%
“…In the obturator group, patients with edentulous upper jaws were included when maxillary defects were rehabilitated with an implant‐supported obturator at Maastricht UMC+ 21 . Maastricht patients were treated according to the “surgical and prosthetic reconsiderations in patients with maxillectomy protocol” as defined by Lethaus et al in 2010 22 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral Health Impact Pro le for Edentulous Patients (OHIP-EDENT), with a higher score meaning poor quality of life, is also used in the latest clinical studies [42][43][44][45][46][47][48] , and thus justifying the great importance of this work and our idea for translation and psychometric properties on the Bosnian language. Therefore, translation and psychometric properties of scales into different languages provides a better clinical outcome for patients using these scales on the maternal language.…”
Section: Discussionmentioning
confidence: 99%